2009
DOI: 10.1103/physrevb.79.153302
|View full text |Cite
|
Sign up to set email alerts
|

Real-time diagrammatic Monte Carlo for nonequilibrium quantum transport

Abstract: We propose a novel approach to nonequilibrium real-time dynamics of quantum impurities models coupled to biased non-interacting leads, such as those relevant to quantum transport in nanoscale molecular devices. The method is based on a Diagrammatic Monte Carlo sampling of the real-time perturbation theory along the Keldysh contour. We benchmark the method on a non-interacting resonant level model and, as a first non-trivial application, we study zero temperature non-equilibrium transport through a vibrating mo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
198
0

Year Published

2010
2010
2021
2021

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 168 publications
(199 citation statements)
references
References 34 publications
(34 reference statements)
1
198
0
Order By: Relevance
“…The interaction expansion based on Eq. (148) is equivalent to the auxiliary field algorithms described by Gull et al (2008) and Werner, Oka, and Millis (2009), as was shown by Mikelsons, Macridin, and Jarrell (2009 (Mühlbacher and Rabani, 2008;Schiró and Fabrizio, 2009;Werner, Oka, and Millis, 2009). We sketch here the derivation for the general impurity model defined in Eq.…”
Section: B Weak-coupling Ctqmcmentioning
confidence: 99%
See 2 more Smart Citations
“…The interaction expansion based on Eq. (148) is equivalent to the auxiliary field algorithms described by Gull et al (2008) and Werner, Oka, and Millis (2009), as was shown by Mikelsons, Macridin, and Jarrell (2009 (Mühlbacher and Rabani, 2008;Schiró and Fabrizio, 2009;Werner, Oka, and Millis, 2009). We sketch here the derivation for the general impurity model defined in Eq.…”
Section: B Weak-coupling Ctqmcmentioning
confidence: 99%
“…This sharp crossover was unexpected because the corresponding equilibrium temperature T eff after the quench is much higher than the critical end point of the Mott metal-insulator transition in equilibrium [T c ≈ 0.055 (Georges et al, 1996), but T eff ¼ 0.84 for U ¼ 3.3]. Interestingly, a good approximation for the critical interaction U dyn c ≈ 3.4 is obtained from a timedependent variational theory using the Gutzwiller approximation Fabrizio, 2010, 2011). A similar strong dependence on the quenched interaction was observed in Heisenberg chains (Barmettler et al, 2009).…”
Section: Interaction Quench In the Hubbard Model Prethermalizatiomentioning
confidence: 99%
See 1 more Smart Citation
“…These shortcomings have motivated us to develop a systematic, numerically exact methodology to study quantum dynamics and quantum transport including many-body effects, in particular, correlated electronic-nuclear dynamics-the multilayer multiconfiguration time-dependent Hartree (ML-MCTDH) theory in second quantization representation (SQR). 79 Other efforts along the same direction include the numerical path integral approach, [80][81][82] real-time quantum Monte Carlo simulations, 83,84 the numerical renormalization group approach, 85 and the time-dependent density matrix renormalization group approach. 86 For a comparison and an overview of various different methods in the related problem of nonequilibrium transport with electron-electron interaction, see Ref.…”
Section: Introductionmentioning
confidence: 99%
“…Though much is known for quantum impurity systems in equilibrium, understanding their properties in non-equilibrium steady-state is still limited. Nevertheless, significant progress has been made by different approaches, such as (1) analytical approximations: perturbative renormalization group method (RG) 27,28 , Hamiltonian flow equations 29 , functional RG 30,31 , strong-coupling expansions 32 , master equations 33 ; (2) exact analytical solutions: field theory techniques 34 , the scattering Bethe Ansatz 35 , mapping of a steady-state non-equilibrium problem onto an effective equilibrium system [36][37][38][39] , non-linear response theory approach to current fluctuations 40 ; (3) numerical methods: time-dependent density matrix renormalization group (RG) 41 , time-dependent numerical RG 42 , diagrammatic Monte Carlo 43 , and imaginary-time nonequilibrium quantum Monte Carlo 44 .…”
Section: Introductionmentioning
confidence: 99%